2022
DOI: 10.1029/2022jb025355
|View full text |Cite
|
Sign up to set email alerts
|

The “New Core Paradox”: Challenges and Potential Solutions

Abstract: The "new core paradox" (Olson, 2013) suggests that the persistence of the geomagnetic field over nearly all of Earth history (Bono et al., 2022;Fu et al., 2021;Tarduno et al., 2020) is in conflict with the core being highly thermally conductive (Pozzo et al., 2022;Williams, 2018), which makes convection and dynamo action in the core much harder prior to the nucleation of the inner core. Older theoretical estimates of the thermal conductivity of high pressure iron around 30-50

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 97 publications
1
8
0
Order By: Relevance
“…This agrees with the findings of (Driscoll and Davies, 2023) who found that a present day radiogenic heat production of ≥ 2 TW and an f viscosity ≤ 10…”
Section: Potassiumsupporting
confidence: 93%
See 1 more Smart Citation
“…This agrees with the findings of (Driscoll and Davies, 2023) who found that a present day radiogenic heat production of ≥ 2 TW and an f viscosity ≤ 10…”
Section: Potassiumsupporting
confidence: 93%
“…All models where Q ppt = 0 fail to maintain E j > 0 prior to inner core nucleation (O'Rourke et al, 2017;Driscoll and Davies, 2023). Similarly, all models where only Mg is extracted through precipitation (O concentration only changes due to inner core growth) also fail in this regard.…”
Section: Mgomentioning
confidence: 99%
“…Using a less sensitive formalism such as Al'Tshuler will at least close one of the point of discussion about the validity of the results: whether or not the values of γ 0 and γ ∞ are the 'true' values, at least the error is low and if differences arise between models, then they are probably not due to the Grüneisen parameter. On the other hand, if the end goal is to best describe the entirety of the phenomenon or get a precise estimate of the core temperature (Driscoll & Davies 2023;Dobrosavljevic et al 2022), then the best formalism is the one that fits the best the data, or the values that are calculated directly within ab initio studies (Vočadlo 2007;Alfè 2009;Alfè et al 2007). If one would use a core segregation model to calculate the actual temperature at the CMB instead of highlighting the correlations between parameters, or actually deriving a precise value on those correlations, then the choice of formalism and parameters value must be driven by the quality of the data, the quality of the fit, and the range of uncertainties on the parameters as highlighted in section 6.2.…”
Section: Assessing the Uncertainties In The Output Of The Modelmentioning
confidence: 99%
“…The intrinsic magnetic fields observed on Earth and terrestrial planets are thought to originate from the convection processes within their metallic liquid cores [1][2][3]. This convection could be driven by thermal or chemical buoyancy depending on the thermal conductivity of the core minerals and the temperature gradient across the core-mantle boundary.…”
Section: Introductionmentioning
confidence: 99%